Communities advancing the studies of Tribal nations across their lifespan: Design, methods, and baseline of the CoASTAL cohort - Tracy, K.; Boushey, Carol; Roberts, S.; Morris, J.; Grattan, L. (2016)
© 2016The CoASTAL cohort represents the first community cohort assembled to study a HAB-related illness. It is comprised of three Native American tribes in the Pacific NW for the purpose of studying the health impacts of chronic, low level domoic acid (DA) exposure through razor clam consumption. This cohort is at risk of DA toxicity by virtue of their geographic location (access to beaches with a history of elevated DA levels in razor clams) and the cultural and traditional significance of razor clams in their diet. In this prospective, longitudinal study, Wave 1 of the cohort was comprised of 678 members across the human lifespan, with both sexes represented within child, adult, and geriatric age groups. All participants were followed annually with standard measures of medical and social history; neuropsychological functions, psychological status, and dietary exposure. DA concentrations were measured at both public and reservation beaches where razor clams are acquired. Multiple metrics were piloted to further determine exposure. Baseline data indicated that all cognitive and psychological functions were within normal limits. In addition, there was considerable variability in razor clam exposure. Therefore, the CoASTAL cohort offers a unique opportunity to investigate the potential health effects of chronic, low level exposure to DA over time.